Attempts in Strengthening Indigenous Justice Systems in Colombia Through Transitional Justice - Angela Marcela Olarte Delgado (International Journal for Crime, Justice and Social Democracy)
This study examines the extent to which transitional justice in Colombia has strengthened Indigenous justice systems. Indigenous peoples in Colombia have suffered the worst violations of human rights due to the armed conflict (1958–2016). Thus, the State has failed to uphold their rights to truth, reparation, justice, and nonrecurrence. The task of the Special Jurisdiction for Peace, the justice component of the transitional justice system, is to prevent cycles of impunity endured by Indigenous communities. It endeavors to address epistemic violence rooted in international and national laws that incorporate intercultural approaches within their regulations and proceedings. However, tensions have emerged due to the challenges that pose the effective understanding of the Indigenous ontologies of damage, justice, and reconciliation in Colombia. The study’s findings demonstrate that strengthening Indigenous justice is dependent on the understanding of its ontology and the capacity of transitional justice to develop legal frameworks based on Indigenous law.